The role of the moral aspect of the administrative accountant In the quality of accounting information - عبد الجنابي, عبد خلف; نوري, مقداد احمد (Journal of Economics and Administrative Sciences, 2014)
The importance of the accounting profession in creating data and accounting information for economic resources and their sources and changes therein , through the effectiveness of this information and the degree of suitability and providing accurate and timely manner and in a form that makes it able to rationalize decisions and performance reporting , and there are several elements and behaviors control how the effectiveness of these reports and these behaviors work ethic that govern the work of management accountant when preparing performance reports , which are the ethics of the work of professional control principles and rules of accounting , legal, such as objectivity and reliability , neutrality and timeliness that must be available in the accounting information , and the ethics of acts of self- control principles and religious belief and customary stems from personal factors related to the environment and society Ttatr within the concepts of justice and a sense of responsibility and faith and devotion and considerate of others ,